The effect of physical exercises to improve muscle strength to reduce recurrent injuries of the ankle joint in men’s high jump - Khaleel, Feryal Sami (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Sports injuries represent a significant threat to athletes’ futures. This study aimed to develop preventive physical exercises focused on enhancing muscular strength within the ankle joint among the research participants. Additionally, it sought to evaluate the effectiveness of these exercises on the muscular strength of the muscles involved in the ankle joint. The study used the experimental method by using the pre and post-experimental design for one experimental group for the research sample. The researcher deliberately selected male high jumpers in the advanced category as the research community, with a sample size of 10 players. SPSS was used for statistical analysis. The results of our study showed significant differences between the pre-test and post-test measurements, highlighting particular interest in the post-tests. The study findings underscore the effectiveness of preventive exercises in averting ankle joint injuries, as evidenced by their positive impact on muscular strength within the ankle joint. Additionally, the results reveal a notable improvement in muscular strength following the implementation of these exercises.